The creative process as interfaith: how contemporary art supports interreligious dialogue in Singapore - Ali Hussain (2024)
Contemporary art is a good example of Tinu Ruparell’s notion of “interstitial interreligious dialogue”, a means to engage and connect through the shared appreciation of art and the creative process. From Beethoven to one of Singapore’s own patron saints, Habib Noh al-Habsyi, countless artists, visionaries and thinkers have emphasised the importance of the artistic channel as a medium to bring harmony to different communities of faith.